UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA DENGAN MENGGUNAKAN TEKNIK SCRAMBLE PADA SISWA KELAS V SEKOLAH DASAR - Nelsya Putri Zalianti; Iis Aprinawati; Rusdial Marta; Afriza Rahma Rani; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability to read comprehension in Indonesian language lessons in class V UPT SDN 013 Muara Jalai. The purpose of this study is to describe the improvement of reading comprehension skills in Indonesian language lessons in Chapter V using the Scramble Technique in class V students of UPT SDN 013 Muara Jalai. This research technique is Classroom Action Research (CAR) which is carried out in two cycles. The data collection techniques in this study are tests, observation, and documentation. This study consists of two cycles where 1 cycle consists of 2 meetings and 4 stages namely planning, implementation, observation, reflection and the time of the study was carried out in September 2025. The subjects of this study were 15 class V students, with 6 boys and 9 girls. Data collection techniques were documentation, observation. The results of this study can be concluded that the ability to read comprehension of students on the material CHAPTER V Love Indonesia Class V UPT SDN 013 Muara Jalai in cycle I meeting I with a percentage of 13.3% with an average value of 45.6, at meeting II increased with a percentage of 46.66% with an average value of 64.8. In cycle II Meeting I reading comprehension of students again increased with a percentage of 86.66% with an average value of 81.6, and at meeting II with a percentage of 100% with an average value of 89.8. Thus it can be concluded that using the Scramble technique can improve students' reading comprehension skills in Indonesian language lessons Material Chapter V Love Indonesia Class V UPT SDN 013 Muara Jalai.